The Concept of Disaster Education and the Roles of Educational Personnel, Parents, Partners, and Community in Early Childhood Education - Dwi Jati Marta; I Dewa Ketut Kerta Widana; Adi Subiyanto; Arry Aditsya Yoga (Lia Center of Research and Education, 2025)
Indonesia faces high disaster risk due to its geological and geographical conditions, which disproportionately affect vulnerable groups, including young children. This situation highlights the urgency of integrating disaster education into Early Childhood Education to build awareness, preparedness, and resilience from an early age. This research aims to examine the concept and implementation of disaster education in Early Childhood Education and to analyze the roles of education personnel, parents, partners and the community in its implementation. Employing a qualitative case study approach, the research was conducted in six ECE institutions in Pangkalpinang City and Bangka Regency, Bangka Belitung Islands Province. Data were collected through in-depth interviews, participatory observation, and document analysis involving 24 informants, including teachers, parents, partner representatives, and community leaders and using the interactive model of Miles, Huberman, and Saldaña. The findings identify two empirically grounded implementation models: comprehensive (holistic) and partial integration, shaped by institutional readiness, educator capacity, and local disaster risk contexts. The research also reveals a collaborative ecosystem in which teachers function as core implementers, school leaders as coordinators, parents as learning reinforcers, and partners and community as technical supporters. These findings demonstrate that disaster education in Early Childhood Education is practiced in adaptive and context-specific forms. This research contributes an ecosystem-based, multi-stakeholder framework to strengthen sustainable disaster preparedness and long-term resilience from early childhood.